Automated SEM Mineralogy and Archaeological Ceramics: Applications in Formative Period Pottery From the Atacama Desert - Riera-Soto, Camila; Agüero, Carolina; González-Maurel, Osvaldo; Uribe, Mauricio; Menzies, Andrew (Frontiers in Earth Science, 2022)
The analysis of archaeological ceramics has rapidly evolved over the last decades by the application of new analytical techniques. An emerging analytical proposal to fully characterise archaeological ceramics using automated SEM mineralogy is presented. A case study is provided of sets of ceramics from the San Pedro de Atacama oases in the Atacama Desert, northern Chile. Ceramic fragments of different typologies (i.e., Los Morros, Loa Café Alisado and San Pedro Negro Pulido) found in the Ghatchi archaeological sites are analysed. Our results include automated mineralogical maps, which are used to define the components that form the ceramic pastes, i.e., clay matrix and non-plastic inclusions, as well as grain size and mineral abundance information. We show that the pastes that define the studied ceramic types are more complex than previously suggested. The overall composition for these pastes corresponds to clay mineral-rich matrices containing non-plastic inclusions, such as mineral grains, crushed ceramic fragments, and sedimentary to igneous rock fragments, that may vary in composition, size, and abundance among the studied ceramic types. This mineralogical information allows us to discuss possible sources of raw materials by comparing these paste components with geological information. Here we interpret Los Morros and Loa Café Alisado as foreign ceramic types to Ghatchi, whereas the San Pedro Negro Pulido fragments found in this site agree well with the pottery paste recipe typically recognised in the San Pedro de Atacama oases. The petrographic-approach employed here supports the automated SEM mineralogy as a valid option for archaeometric studies of ceramic pastes since includes precise quantitative data formulated from the chemical composition of each component of the paste, which may provide valuable evidence into raw materials and technological styles.